Modified sodium ion battery positive electrode material, preparation method thereof and sodium ion battery

By forming an A-rich spinel phase composite coating on the layered oxide surface of the positive electrode material of the sodium ion battery, and reintroducing Na+ by high-temperature solid-phase sintering method, the structural instability and residual alkali problems of sodium ion battery are solved. , improves battery capacity and cycle stability, and is suitable for industrial production.

CN119252900APending Publication Date: 2025-01-03湖州超钠新能源科技有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411412401.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The structure of the positive electrode material of sodium ion battery is prone to irreversible phase change during charging and discharging, resulting in rapid attenuation of the battery capacity, and ion exchange between Na+ and H+ in the air, forming residual alkali affects the rateability and cycle stability of the battery.

Method used

Modified sodium ion battery positive electrode material adopts core-shell structure, by forming an A-rich spinel phase composite coating on the surface of layered oxide NaxTMO2, combined with high-temperature solid phase sintering method, the surface Na+ is reintroduced to reduce residual alkali content and improve structural stability.

Benefits of technology

It improves the rate performance and cycle stability of sodium ion batteries, improves battery capacity, simplifies the preparation process, reduces production costs, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252900A_ABST
    Figure CN119252900A_ABST
Patent Text Reader

Abstract

The invention discloses a modified sodium ion battery positive electrode material, a preparation method thereof and a sodium ion battery. The modified sodium ion battery positive electrode material is of a core-shell structure, takes NaxTMO2 as a core, and takes an A-rich spinel phase compound as a coating layer; the chemical formula is NaxTMO2 (at) A, NaxTMO2 is a layered oxide, x is larger than or equal to 0.5 and smaller than or equal to 1.2, TM is an electrochemical active and / or non-active metal element, and A is an A-rich spinel phase compound. A uniform A-rich spinel phase compound is formed on the surface of the layered oxide NaxTMO2 by adopting a high-temperature solid-phase sintering method, so that the interface conductivity of particles can be effectively improved, the air stability of the positive electrode material can be improved, and the rate capability and the cycling stability of the sodium ion battery can be further improved; and at a high temperature, sodium carbonate, sodium hydroxide and other residual alkalis are decomposed, and free Na < + > on the surface enters a material body phase again, so that structural recombination is realized, the residual alkali content is reduced, the capacity of the sodium ion battery is improved, and the processing performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a modified sodium ion battery positive electrode material and a preparation method thereof, and a sodium ion battery. Background Art

[0002] In recent years, with the widespread application of lithium-ion batteries, problems such as shortage of metallic lithium resources, uneven distribution and high cost have become increasingly prominent. Compared with lithium, sodium in the same main group has the advantages of abundant reserves, wide distribution and low cost. Therefore, sodium-ion batteries are considered to be the next generation of large-scale energy storage devices. Sodium-ion batteries are batteries that use the insertion and extraction process of sodium ions between positive and negative electrodes to achieve charging and discharging. Among them, the positive electrode material of sodium-ion batteries is an important component of sodium-ion batteries, responsible for providing active sodium ions, which mainly include layered oxide type (nickel-based / copper-based / iron-based / manganese-based), polyanion type, Prussian blue / white type, etc. However, there are still some key problems that need to be solved in the positive electrode materials of sodium-ion batteries: the structure is prone to irreversible phase changes during charging and discharging, causing the battery capacity to decay rapidly; Na in the positive electrode material + With H in air + Ion exchange occurs, Na + After being released, it reacts with H2O or CO2 in the air to form residual alkali such as NaOH or Na2CO3 on the surface of the material, affecting the battery's rate capability and cycle stability.

[0003] There are two main solutions to the above problems: cation doping (Li, Mg, Ti, Cu, Zn, etc.) and surface coating (Al2O3, TiO2, etc.). Among them, cation doping can regulate the Na interlayer spacing, and the reduced Na interlayer spacing can act as a physical barrier to inhibit the intercalation of water and CO2 molecules in the air and the Na + Spontaneous extraction from the bulk phase; however, it should be considered that the weak hybridization of TM 3d and O 2p orbitals will weaken the TM-O bond, thereby deteriorating stability over a long period of time. Surface coating strategies can improve the air stability of layered oxides, but it is still necessary to consider that blocking the insertion pathway of H2O / CO2 molecules also hinders the Na + The negative impact of embedded active channels and inactive oxides on material conductivity and specific capacity remains unresolved.

[0004] For example, the invention patent with application publication number CN 116404145 A discloses an alumina-coated layered sodium ion positive electrode material and a sodium ion battery. 0.612 K 0.056 MnO2 can isolate the direct contact between the electrolyte and the active material, inhibiting the 3+The dissolution of the material can improve the cycle life of the material; however, its preparation method is relatively complicated, the preparation cycle is long, and the production cost is high. Summary of the invention

[0005] To solve the above problems, in a first aspect, the present invention provides a modified sodium ion battery positive electrode material, which has a higher capacity and good air stability.

[0006] The technical solution of the present invention to solve the above problems is as follows:

[0007] A modified sodium ion battery positive electrode material, wherein the modified sodium ion battery positive electrode material is a core-shell structure, with Na x TMO2 core, with an A-rich spinel phase composite as coating; chemical formula is Na x TMO2@A, where: Na x TMO2 is a layered oxide, the value of x is 0.5≤x≤1.2, TM is an electrochemically active and / or inactive metal element, and A is an A-rich spinel phase composite.

[0008] Preferably, the TM is selected from at least one of Ni, Co, Cu, Fe, Mn, Ti, V, Cr, Mg, Ca, B, Al, Zn, La, Zr, W, Mo, Sr, Y, Cd, Sn, Sb, Ce, and Li.

[0009] Preferably, the Na x TMO2 includes nickel-based, copper-based, manganese-based, and iron-based positive electrode materials; the Na x TMO2 is Ni 2+ / Ni 3+ / Ni 4+ , Cu 2+ / Cu 3+ , Fe 3+ / Fe 4+ , Mn 3+ / Mn 4+ , O 2- / O - Layered oxide cathode materials for charge storage via valence change.

[0010] Preferably, the Na x TMO2 has a P phase, O phase or PO mixed phase crystal structure.

[0011] Preferably, A is selected from at least one of La, Ce, Pr, Nd, Pm, Sm, Eu, Al, Si, Cr, Li, Mn, Fe, Co, Ni, Cu, Zn, Y, Mg, Ca, and In.

[0012] In a second aspect, the present invention also provides a method for preparing the modified sodium ion battery positive electrode material, comprising the following steps:

[0013] S1, Na x TMO2 and source A are thoroughly mixed to obtain a mixture;

[0014] S2. placing the mixture in an air atmosphere furnace for solid phase sintering to obtain a modified sodium ion battery positive electrode material.

[0015] In the process of preparing the positive electrode material of the layered sodium ion battery, it is inevitable that residual alkali such as sodium carbonate and sodium hydroxide will be produced on the surface of the positive electrode material; the residual alkali causes the positive electrode slurry to gel or solidify easily, affecting the coating performance of the positive electrode slurry and the electrochemical performance of the positive electrode sheet and the sodium ion battery. x TMO2 reacts with the residual alkali on the surface at high temperature, and the free Na ions on the surface re-enter the bulk phase of the positive electrode material to achieve structural reorganization; the A source reacts with Na x The surface elements of TMO2 or the A source itself undergoes a solid phase reaction to form an A-rich spinel phase composite coating.

[0016] Preferably, the A source is selected from at least one of the oxides and salts of La, Ce, Pr, Nd, Pm, Sm, Eu, Al, Si, Cr, Li, Mn, Fe, Co, Ni, Cu, Zn, Y, Mg, Ca, and In.

[0017] Preferably, the mass of the A source does not exceed Na x 15% of TMO2 mass.

[0018] Preferably, in step S2, the solid phase sintering temperature is 850-1200° C., and the solid phase sintering time is 2-6 hours.

[0019] Preferably, in step S2, the heating rate of solid phase sintering is 1-8°C / min.

[0020] In a third aspect, the present invention further provides a sodium ion battery, wherein the positive electrode material of the sodium ion battery comprises the above-mentioned modified sodium ion battery positive electrode material.

[0021] The present invention has the following beneficial effects:

[0022] (1) The present invention adopts a high temperature solid phase sintering method to form a layered oxide positive electrode material Na x The surface of TMO2 forms a uniform A-rich spinel phase complex, which can effectively improve the interfacial conductivity of the particles and the air stability of the cathode material, thereby improving the rate performance and cycle stability of the sodium-ion battery.

[0023] (2) By adopting the high-temperature solid-phase sintering method, residual alkali such as sodium carbonate and sodium hydroxide decomposes at high temperature, and the free Na + Re-enter the material phase to achieve structural reorganization, reduce the residual alkali content, increase the capacity of the sodium ion battery, and improve the processing performance;

[0024] (3) The preparation method of the modified sodium ion battery positive electrode material of the present invention has a short sintering cycle and low cost, can effectively improve production capacity, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The nickel-iron-based oxide positive electrode material (Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2) SEM image;

[0026] Figure 2 The modified sodium ion battery positive electrode material (Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 SEM image of O2@Al-rich spinel phase composite). DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] Nickel-iron-based oxide cathode material Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2 is used as the matrix and surface modification is performed. The modification method comprises the following steps:

[0030] S1, 200g of positive electrode material Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2 and 10 g of Al2O3 are fully mixed on a high-speed mixing device to obtain a mixture;

[0031] S2, placing the mixture in an air atmosphere furnace, heating it to 1000°C at a heating rate of 5°C / min, and calcining it for 4 hours to obtain a modified sodium ion battery positive electrode material Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2@Al-rich spinel phase composite.

[0032] Figure 1 Nickel-iron-based oxide positive electrode material (Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2) SEM image; Figure 2 Modified sodium ion battery cathode material (Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 SEM image of O2@Al-rich spinel phase composite). Figure 1 and Figure 2 It can be seen that after surface modification, a smooth and uniform coating layer is formed on the surface of the material particles.

[0033] Example 2

[0034] Manganese iron-based cathode material NaFe 0.1 Mn 0.9 O2 is used as the matrix and surface modification is performed. The modification method comprises the following steps:

[0035] S1, 500g of positive electrode material NaFe 0.1 Mn 0.9 O2 and 40 g of CuO are fully mixed on a high-speed mixing device to obtain a mixture;

[0036] S2, placing the mixture in an air atmosphere furnace, heating it to 1010°C at a heating rate of 5°C / min, and calcining it for 3h to obtain a modified sodium ion battery positive electrode material NaFe 0.1 Mn 0.9 O2@Cu-rich spinel phase composite.

[0037] Example 3

[0038] Manganese copper based cathode material NaCu 0.1 Mn 0.9 O2 is used as the matrix and surface modification is performed. The modification method comprises the following steps:

[0039] S1, 5000g of positive electrode material NaCu 0.1 Mn 0.9 O2 and 200 g of CuO are fully mixed on a high-speed mixing device to obtain a mixture;

[0040] S2, placing the mixture in an air atmosphere furnace, heating it to 980°C at a heating rate of 5°C / min, and calcining it for 4 hours to obtain a modified sodium ion battery positive electrode material NaCu 0.1 Mn 0.9 O2@Cu-rich spinel phase composite.

[0041] Comparative Example 1

[0042] Directly convert the nickel-iron-based layered oxide positive electrode material Na 0.84 Ni 0.13 Fe 0.38 Mn 0.49 O2 is used as the cathode material for sodium-ion batteries.

[0043] Comparative Example 2

[0044] Directly convert the manganese iron-based cathode material NaFe 0.1 Mn 0.9 O2 is used as the positive electrode material for sodium ion batteries.

[0045] Comparative Example 3

[0046] Directly convert the manganese-copper-based positive electrode material NaCu 0.1 Mn 0.9 O2 is used as the cathode material for sodium-ion batteries.

[0047] The modified sodium ion battery positive electrode materials in Examples 1 to 3 and the sodium ion battery positive electrode materials in Comparative Examples 1 to 3 were respectively prepared into button batteries, and the electrical performance of the obtained button batteries was tested.

[0048] Preparation method of button cell: The positive electrode materials in Examples 1 to 3 and Comparative Examples 1 to 3 were respectively used as active materials, mixed according to the mass ratio of active material: SP: PVDF of 8:1:1, NMP was added to make a viscous slurry, coated on aluminum foil, and baked in a vacuum oven at 100°C for 12h to obtain a positive electrode sheet. A sodium metal sheet was used as a negative electrode sheet, glass fiber (Waterman) was used as a diaphragm, and 1 mol / L NaPF6 (the solvent was EC and DMC in a volume ratio of 1:1) was used as an electrolyte to assemble a 2032 button cell in an Ar protective glove box.

[0049] Button cell test conditions: Test the battery in the voltage range of 2.0-4.0V: ① 0.1C activation for three cycles, record the 0.1C first cycle discharge capacity; ② 0.1C activation for three cycles, cycle the activated battery at 5C for three cycles, record the third cycle discharge capacity, and calculate the 5C / 0.1C rate performance; ③ 0.1C activation for three cycles, cycle the activated battery at 1C for 50 cycles, record the 50th cycle discharge capacity retention rate. The test results are as follows:

[0050] Table 1: Button battery electrical performance test data table

[0051]

[0052] It can be seen from Table 1 that the specific capacity, rate performance, and cycle retention rate of the button battery made with the modified sodium ion battery positive electrode material in Example 1 as the active material are better than those of Comparative Example 1; the specific capacity, rate performance, and cycle retention rate of the button battery made with the modified sodium ion battery positive electrode material in Example 2 as the active material are better than those of Comparative Example 2; the specific capacity, rate performance, and cycle retention rate of the button battery made with the modified sodium ion battery positive electrode material in Example 3 as the active material are better than those of Comparative Example 3;

[0053] In summary, the sodium ion battery positive electrode material obtained by the modification method of the present invention has high specific capacity and excellent rate performance and cycle stability.

Claims

1. A modified sodium ion battery positive electrode material, characterized in that: The modified sodium ion battery positive electrode material is a core-shell structure with Na x TMO2 core, with an A-rich spinel phase composite as coating; chemical formula is Na x TMO2@A, where: Na x TMO2 is a layered oxide, the value of x is 0.5≤x≤1.2, TM is an electrochemically active and / or inactive metal element, and A is an A-rich spinel phase composite.

2. A modified sodium ion battery positive electrode material according to claim 1, characterized in that: The TM is selected from at least one of Ni, Co, Cu, Fe, Mn, Ti, V, Cr, Mg, Ca, B, Al, Zn, La, Zr, W, Mo, Sr, Y, Cd, Sn, Sb, Ce, and Li.

3. A modified sodium ion battery positive electrode material according to claim 1, characterized in that: The Na x TMO2 includes nickel-based, copper-based, manganese-based, and iron-based positive electrode materials; the Na x TMO2 is Ni 2+ / Ni 3+ / Ni 4+ , Cu 2+ / Cu 3+ , Fe 3+ / Fe 4+ , Mn 3+ / Mn 4+ , O 2- / O - Layered oxide cathode materials for charge storage via valence change.

4. The modified sodium ion battery positive electrode material according to claim 1, characterized in that: The A is selected from at least one of La, Ce, Pr, Nd, Pm, Sm, Eu, Al, Si, Cr, Li, Mn, Fe, Co, Ni, Cu, Zn, Y, Mg, Ca, and In.

5. The method for preparing the modified sodium ion battery positive electrode material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, Na x TMO2 and source A are thoroughly mixed to obtain a mixture; S2. placing the mixture in an air atmosphere furnace for solid phase sintering to obtain a modified sodium ion battery positive electrode material.

6. The preparation method according to claim 5, characterized in that: The A source is selected from at least one of the oxides and salts of La, Ce, Pr, Nd, Pm, Sm, Eu, Al, Si, Cr, Li, Mn, Fe, Co, Ni, Cu, Zn, Y, Mg, Ca, and In.

7. The preparation method according to claim 5, characterized in that: The mass of the source A does not exceed Na x 15% of TMO2 mass.

8. The preparation method according to claim 5, characterized in that: In the step S2, the solid phase sintering temperature is 850-1200° C., and the solid phase sintering time is 2-6 hours.

9. The preparation method according to claim 8, characterized in that: In the step S2, the heating rate of the solid phase sintering is 1-8°C / min.

10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery includes the modified positive electrode material of the sodium ion battery described in any one of items 1 to 4.

Citation Information

Cited By

  • Preparation method and application of sodium ion battery composite positive electrode material

    CN120483278A